Seismic velocity and attenuation structures of the Queen Charlotte Basin from full-waveform tomography of seismic reflection data - Takam Takougang, Eric; Calvert, A. (Society of Exploration Geophysics, 2012)
We applied viscoacoustic waveform tomography to four seismic reflection lines from the central and northern part of the Queen Charlotte sedimentary basin and, using frequencies of 7–12 Hz, we estimated the compressional velocity and attenuation above a depth of approximately 1.2 km. We refined our previously published inversion strategy by alternating between phase-only and amplitude-plus-phase velocity inversion for the first two pairs of frequencies used, and added a second step, in which we inverted for attenuation from the lowest frequency using the final recovered velocity model and an initial homogeneous Qp-model. Our recovered velocity and attenuation models demonstrated an overall good correlation with the available sonic and gamma-ray logs. Modeled seismic data matches the field data well and 1D velocity and attenuation profiles extracted at line intersections show a good correlation, thus demonstrating the robust nature of the results.Recovered velocities aid in interpreting shallow structures not readily identifiable on the conventional migration such as Quaternary strata and Pliocene faulting. Recovered attenuation values in the sedimentary rocks are generally consistent with saturated sandstones and consistent with the geology interpreted from well logs. Localized regions of elevated attenuation and associated low velocities correlate with siltstones and shales, the presence of hydrocarbons, or inferred increases in porosity due to fracturing. Seafloor pockmarks, where venting of gas occurs, are underlain by low velocities and an anomalous attenuation variation, and pipe-like gas chimneys are interpreted in two other areas of Hecate Strait. Igneous basement is associated with high velocity and high attenuation in its uppermost part, suggesting the presence of volcanic rocks, but the elevated attenuation may also be due to scattering and elastic mode conversions not included in the viscoacoustic inversion.